Physiological Response of Soybean Plants to Water Deficit - Wang, Xiyue; Wu, Zihao; Zhou, Qi; Wang, Xin; Song, Shuang; Dong, Shoukun (Frontiers in Plant Science, 2022)
Soybean is an important cash crop in the world, and drought is the main reason for the loss of soybean plants productivity, drought stress during the most water-sensitive flowering period of soybeans. In this paper, drought tolerant variety Heinong 44 (HN44) and sensitive variety Heinong 65 (HN65) were used as experimental materials. Drought treatment was carried out at the early flowering stage. The method of controlling soil moisture content was used to simulate different degrees of drought, and the physiological changes of the two varieties of Soybean under different soil moisture content were studied. The results showed that with the decrease of soil moisture content, the content of malondialdehyde in soybean leaves increased significantly, the activities of POD, CAT and APX increased first and then decreased, the contents of proline, soluble sugar and soluble protein increased, and the total antioxidant capacity increased significantly. When the soil moisture content was 15.5%, the degree of membrane lipid peroxidation, osmotic regulatory substances, antioxidant enzyme activity and total antioxidant capacity increased the most, and the decrease of drought tolerant variety HN44 was significantly less than that of sensitive variety HN65. Our research reveals the response law of soybean crops to physiological characteristics under water deficit, and provides theoretical basis and guiding significance for drought resistant cultivation and breeding of soybean.